Pengaruh Brand Loyalty dan Karakteristik Muzakki terhadap Keputusan Berzakat melalui Aplikasi Shopee - Galang Yoga Prawira (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
This purpose of this sudies to determine the effect of brand loyalty and muzakki characteristics on muzakki decisions through Shopee. There are several things that influence a muzakki to choose a place to distribute his zakat. Some of these include brand loyalty to measure a person's determination to always choose a place for zakat distribution. The second is the characteristics of muzakki, one of which measures what influences muzakki to choose a zakat institution. This study used quantitative approach by path analysis to look for causal relationships. The population taken for this study is the muzakki around the researcher's environment. The sample used is 125 respondents using hair techniques by multiplying 5-10 times the number of research indicators. The sampling technique used in this study is probability sampling, where each population has the same opportunity to take data. The results shows that the variable brand loyalty and muzakki characteristics have a significant effect on muzakki's decision to give zakat through Shopee.